2021
DOI: 10.1177/13623613211045596
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging telehealth to evaluate infants with prodromal autism spectrum disorder characteristics using the telehealth evaluation of development for infants

Abstract: This study investigated the feasibility of recruiting and assessing infants with prodromal autism characteristics in the first year of life via telehealth. Participants included 41 infants (Mage = 10.51 months, 51.2% female, 80.5% White) whose parents had concerns about social communication delays or autism. All infants met concerns criteria on a social communication screener. Infants were subsequently assessed via telehealth using the Telehealth Evaluation of Development for Infants protocol, wherein parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The Telehealth Evaluation of Development for Infants (TEDI; Talbott et al, 2019; Talbott, Dufek, et al, 2022) is a tele-assessment protocol adapted from laboratory-based measures of early autism characteristics (e.g., AOSI), communication, language, play, and other related developmental domains. It was developed prior to the pandemic to evaluate infants 6 to 12 months of age.…”
Section: Future Directions In Autism Assessmentmentioning
confidence: 99%
“…The Telehealth Evaluation of Development for Infants (TEDI; Talbott et al, 2019; Talbott, Dufek, et al, 2022) is a tele-assessment protocol adapted from laboratory-based measures of early autism characteristics (e.g., AOSI), communication, language, play, and other related developmental domains. It was developed prior to the pandemic to evaluate infants 6 to 12 months of age.…”
Section: Future Directions In Autism Assessmentmentioning
confidence: 99%
“…See Berger et al (2021) for a review of these tools. The Telehealth Evaluation of Development for Infants (TEDI; Talbott et al, 2020Talbott et al, , 2021) is a parent coaching protocol for conducting a social communication-focused developmental assessment for infants. In the full protocol, parents are coached through a series of semi-structured play activities designed to allow for the scoring of standardized tools, including the Autism Observation Scale for Infants (AOSI; Bryson et al, 2008) and the P-ESDM Infant-Toddler Curriculum Checklist (ITCC; Rogers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the full protocol, parents are coached through a series of semi-structured play activities designed to allow for the scoring of standardized tools, including the Autism Observation Scale for Infants (AOSI; Bryson et al, 2008) and the P-ESDM Infant-Toddler Curriculum Checklist (ITCC; Rogers et al, 2020). See Talbott et al (2021) for a more detailed description of the play activities and protocol. Initial pilot studies of the TEDI reported high inter-rater agreement (ICC’s of .94 and .89) and low to moderate test–retest reliability ( r = .46 and .25 ) for the AOSI and the ITCC in a sample of 6- to 12-month-olds with early social communication concerns (Talbott et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current paper, we sought to gain a greater understanding of telehealth-based evaluations of infants’ development by qualitatively analyzing written feedback from caregivers participating in ongoing study of one such telehealth protocol, the Telehealth Evaluation of Development for Infants (TEDI; Talbott, Dufek, Young, and Rogers 2021 , Talbott et al, 2020 ). The TEDI protocol was initially developed prior to the COVID-19 pandemic in an effort to translate laboratory-based measures of early ASD characteristics, communication, language, play, and other related developmental domains into a telehealth format.…”
mentioning
confidence: 99%